Differences in interest between male and female students toward badminton learning - Andika Panji Pratama; Nur Ahmad Arief; Andika Panji Pratama; Nur Ahmad Arief (Citius : Jurnal Pendidikan Jasmani, Olahraga, dan Kesehatan, 2026)
Student interest is a critical determinant of participation and achievement in physical education, yet gender-based differences in this interest remain underexplored at the junior high school level. This study examined the difference in interest between male and female students toward badminton learning among seventh-grade students at SMP Negeri 1 Malo. This research employed a quantitative approach with a comparative design. The research sample consisted of 136 students, including 63 male students and 73 female students. Data were collected using a questionnaire measuring students’ interest in badminton learning, consisting of 38 statements based on a Likert scale. Before testing the hypotheses, prerequisite tests including normality and homogeneity tests were conducted. The normality test using the Shapiro–Wilk method showed significance values of 0.236 for male students and 0.302 for female students, indicating that the data were normally distributed. The homogeneity test using Levene’s Test produced a significance value of 0.744, indicating that the variances of the two groups were homogeneous. Hypothesis testing using the Independent Samples T-Test resulted in a significance value of 0.000 (p < 0.05), indicating a significant difference in interest between male and female students toward badminton learning, with female students demonstrating higher interest scores than male students. The findings suggest that gender is one of the factors influencing students’ interest in physical education at school. Therefore, physical education teachers are encouraged to design engaging and inclusive learning strategies to enhance students’ interest and participation in sport activities.